Seismic velocities, anisotropy and deformation in Siberian cratonic mantle: EBSD data on xenoliths from the Udachnaya kimberlite - Bascou, J.; Doucet, Luc-Serge; Saumet, S.; Ionov, D.; Ashchepkov, I.; Golovin, A. (Elsevier BV, 2011)
The study presents microstructures and crystallographic preferred orientations (CPO) of minerals obtained by electron back-scattered diffraction (EBSD) in a suite of 23 fresh mantle xenoliths (20 peridotites, 2 eclogites and 1 pyroxenite) from the Udachnaya kimberlite in central Siberian craton. The suite includes coarse spinel- and garnet-facies peridotites equilibrated at 760-1000°C from the upper part of the mantle lithosphere (45-160km) and porphyroclastic garnet peridotites from the base of the lithosphere (160-210km; 1200-1320°C). The data indicate that dislocation creep is the main deformation mechanism in the peridotites and eclogites. The CPO patterns of olivine suggest a dominant activation of the (010) [100] slip system. Within this general pattern, coarse peridotites show a better alignment of [100] -olivine while porphyroclastic rocks have a better alignment of [010]-olivine. Recrystallization in the porphyroclastic peridotites reduces olivine grain size and facilitates the development of a mosaic matrix that leads to a decrease in the CPO strength. Orthopyroxene in peridotites slips parallel to (100) [001] ; clinopyroxene shows a clear slip direction on [001] in both peridotites and eclogites. Seismic properties estimated from the CPO data and modal abundances of major minerals show significant differences between peridotites, eclogites and pyroxenites; some differences also exist between peridotite types. Importantly, coarse peridotites have much higher anisotropy than eclogites and may yield higher P-wave velocities in the fast direction (V p =8.8km/s). Thus, the extremely high sub-Moho velocities (V p > 8.7km/s) reported from some seismic profiles in the Siberian craton can be better explained by strong anisotropy of coarse peridotites in a horizontally foliated mantle rather than by the presence of abundant eclogites. © 2010 Elsevier B.V.